2014
DOI: 10.1177/0049124114532446
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies Nested in Fuzzy-set QCA on Sufficiency

Abstract: Qualitative Comparative Analysis (QCA) is a method for cross-case analyses that works best when complemented with follow-up case studies focusing on the causal quality of the solution and its constitutive terms, the underlying causal mechanisms, and potentially omitted conditions. The anchorage of QCA in set theory demands criteria for follow-up case studies that are different from those known from regression-based multimethod research (MMR). Based on the evolving research on set-theoretic MMR, we introduce pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(23 citation statements)
references
References 56 publications
0
22
0
1
Order By: Relevance
“…The fussy-set multiple conjunctural analysis is able to analyze the combination of causal conditions when compared to the existing qualitative methods, without an assumption of the independence between variables and the linear relationship. As a result, through the fussy-set multiple conjunctural analysis, this study has the strength of analyzing causal relationship by integrating not only the unilineal effects by certain variables, but also multiple causal conditions [38][39][40].…”
Section: Methodsmentioning
confidence: 99%
“…The fussy-set multiple conjunctural analysis is able to analyze the combination of causal conditions when compared to the existing qualitative methods, without an assumption of the independence between variables and the linear relationship. As a result, through the fussy-set multiple conjunctural analysis, this study has the strength of analyzing causal relationship by integrating not only the unilineal effects by certain variables, but also multiple causal conditions [38][39][40].…”
Section: Methodsmentioning
confidence: 99%
“…More systematic use of independent data sets and multiple methods for validation purposes represents a promising avenue for future archetype analysis. Some of the methods addressed in this study can provide examples in these respects, for instance with reference to the use of case studies that explore QCA results (Schneider and Rohlfing 2016) and recent contributions https://www.ecologyandsociety.org/vol24/iss3/art34/ that link QCA and process tracing (Schneider and Rohlfing 2013), and embedding these in mixed-method research (Rohlfing and Schneider 2018).…”
Section: Frontier Vi: Validationmentioning
confidence: 99%
“…The Fuzzy-set Analysis (methodology) is a special form of case study method as Qualitative Comparative Analysis (QCA) suggested by Zadeh from the University of Berkeley in 1965, and it has been used in diverse ways by scholars such as Ragin and Kvist in application to Social Sciences [29,30]. The Fuzzy-set analysis is an improved version of the method from Qualitative Comparative Analysis [31,32] that was previously used in the Social Sciences.…”
Section: The Rationale Of Fuzzy-set and Ideal Type Analysismentioning
confidence: 99%
“…Second, due to this property, Fuzzy-set analysis enables dealing of the middle-case studies (15-25 cases), which comparative case analysis and regression analysis could not address despite being substantial subjects for analysis, and makes middle-class comparative analysis possible [29,31]. Moreover, it is also used in analyzing joint causal relations by paying due consideration to interactive effects between each quality in a given case [29,30]. Third, it can explain diverse social phenomena.…”
Section: The Rationale Of Fuzzy-set and Ideal Type Analysismentioning
confidence: 99%